Procedural norms in the financially – legal regulation - Kasianenko, Liubov Mykhailivna; Latkovska, Tamara Anatoliivna (Taras Shevchenko National University of Kyiv, 2019)
The monograph considers the concept of legal norms. Financial-procedural norms are legal norms that are inherent in all the qualities of the legal norm, and at the same time they also have special qualities that are characteristic only of financial-procedural norms. There are many financial and procedural rules in Ukraine that require more clear legislative regulation.

У розділі монографії розглядається поняття правових норм. Фінансово-процесуальні норми є правовими нормами, яким властиві всі якості правової норми, і в той же час вони мають також особливі якості, які характерні лише для фінансово-процесуальних норм. В Україні існує багато фінансово-процедурних норм, які потребують більш чіткого законодавчого регулювання.
Keywords: financial - legal regulation; legal norms; фінансово - правове регулювання; правові норми